Prophylactic administration of intravenous Ceftriaxone before incision or after cord clamping during Caesarean Section A comparative study - Nazrina, Sayeda; Islam, Md Manowarul; Chisty, Shahnur; Maruf, Abdullah Al (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Prophylactic antibiotic is recommended to reduce infection-related complication following caesarean section. There is a current debate on the timing of administration of prophylactic antibiotic in caesarean delivery Objectives: To assess the impact of timing of antibiotic prophylaxis at caesarean section before skin incision versus after cord clamping on clinically detectable maternal and neonatal infectious morbidity. Study design: Prospective randomized trial. Methods: One twenty pregnant women who underwent emergency and elective caesarean section were randomly assigned into 2 groups. Group A (n=60) patients received 1 gm ceftriaxone intravenously 30 minutes before skin incision and group B (n=60) received 1 gm ceftriaxone intravenously after umbilical cord clamping and delivery of the baby. Both groups received ceftriaxone 1 gm intravenously daily for 3 days followed by oral tablet cefuroxime 250 mg 12 hourly for next 2 days. Both groups were observed regarding maternal febrile morbidity, endometritis, wound infection, and urinary tract infection (UTI); the neonates were observed for low APGAR score, jaundice, clinically detectable neonatal sepsis and admission to neonatal ward. Results: Both groups were comparable regarding maternal age, body weight, gestational age, parity and indications of cesarean section. The number of cases who had febrile morbidity, endometritis, wound infection, and UTI were almost similar between two groups and these differences were not statistically significant (p=0.27, 0.21, 0.37 and 0.17 respectively). No difference was found between both groups regarding low APGAR score, jaundice, clinically detectable neonatal sepsis and admission to neonatal ward (p=0.17, 0.41, 0.21, 0.53 respectively). Conclusion: There were no differences in maternal infectious morbidity and neonatal outcome after administration of prophylactic antibiotic ceftriaxone pre-incision or post-clamping of the umbilical cord for caesarean delivery. J. Dhaka National Med. Coll. Hos. 2017; 23 (02): 19-22